1974
DOI: 10.1037/h0036732
|View full text |Cite
|
Sign up to set email alerts
|

Therapy set: Its effects on subjects' involvement in systematic desensitization and treatment outcome.

Abstract: The present study tested the hypothesis that therapy instructions significantly augment desensitization treatment effects by influencing subjects' involvement in the conditioning procedure. College snake phobics were randomly assigned to one of four treatment groups or a no-treatment control. Therapy set and involvement instructions were manipulated within a 2X2 factorial design in order to create therapeutically and experimentally oriented subjects who were either unencouraged or encouraged to work hard at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

1976
1976
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…A number of studies have been addressed to the role of expectancy in systematic desensitization (see reviews by Borkovec, 1973b;Lick & Bootzin, 1975;Rosen, 1976). Even though these studies seem to offer conflicting results, Rosen (1974Rosen ( , 1976 has suggested that much of the conflict can be resolved by distinguishing between two types of expectancy manipulations. In the first type, all subjects are informed that they are receiving a treatment procedure.…”
Section: University Of Kansasmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies have been addressed to the role of expectancy in systematic desensitization (see reviews by Borkovec, 1973b;Lick & Bootzin, 1975;Rosen, 1976). Even though these studies seem to offer conflicting results, Rosen (1974Rosen ( , 1976 has suggested that much of the conflict can be resolved by distinguishing between two types of expectancy manipulations. In the first type, all subjects are informed that they are receiving a treatment procedure.…”
Section: University Of Kansasmentioning
confidence: 99%
“…A total of nine studies (Lomont & Brock, 1971;Marcia, Rubin, & Efran, 1969;Mc-Glynn, 1971;McGlynn & Mapp, 1970;Mc-Glynn, Mealiea, & Nawas, 1969;McGlynn, Reynolds, & Linder, 1971b;McGlynn & Williams, 1970;Rosen, 1974;Wilson & Thomas, 1973) have failed to show significant differences between positive therapeutic instructions and neutral or negative therapeutic instructions accompanying desensitization. In addition, several studies have failed to find differences resulting from positive, neutral, and negative therapeutic expectancies when these differential expectancies were brought about through the administration of "therapy-boosting" placebo drugs (Woy & Efran, 1972) or bogus physiological feedback (Hewlett & Nawas, 1971;McGlynn, 1972;Nawas, 1972).…”
Section: University Of Kansasmentioning
confidence: 99%
See 3 more Smart Citations